Estudo da sinterização e oxidação anódica na produção de um capacitor eletrolítico de nióbio - Nascimento, Edson Silva do (2016)
It seeks to find an alternative to the current tantalum electrolytic capacitors in the market due to its high cost. Niobium is a potential replacement for be lighter and cheaper than tantalum. They belong to the same table group periodically and thus exhibit several physical and chemical properties similar. Niobium is used in many technologically important applications, and Brazil has the largest reserves, around 96%. These electrolytic capacitors have high specific capacitance, so they can store high energy in small volumes compared to other types of capacitors. This is the main attraction of this type of capacitor because is growing demand in the production of capacitors with capacitance specifies increasingly high, this because of the miniaturization of various devices such as GPS devices, televisions, computers, phones and many others. The production route of the capacitor was made by powder metallurgy. The initial niobium poder was first characterized by XRD, SEM and laser particle size to then be sieved into particle size 400mesh. The powder was then compacted at pressure of 150MPa and sintered at 1400, 1450 and 1500°C using two sintering time 30 and 60min. Sintering is an important part of the process as it affects properties as porosity and surface cleaning of the samples, which greatly affected the quality of the capacitor. After sintering the samples were underwent a process of anodic oxidation (anodizing), which created a thin film of niobium pentoxide over the whole surface of the sample, this film is the dielectric capacitor. The anodizing process variables influenced a lot in film formation and consequently the capacitor. The samples were characterized by electrical measurements of capacitance, loss factor and ESR (equivalent series resistance). The sintering has affected the porosity and in turn the specific area of the samples. The capacitor area is directly related to the capacitance, that is, the higher the specific area is the capacitance. Higher sintering temperatures decrease the surface area but eliminate as many impurities. The best results were obtained at a temperature of 1400°C with 60 minutes. The most interesting results were compared with the specific capacitance and ESR for all samples.